A Bitter Medicine? Short-term Employment Impact of Deregulation in Network Industries - Andrea Bassanini (Institute for the Study of Labor (IZA), 2015)
There is evidence that pro-competitive reforms in an industry with large incumbents induce the latter to re-organise and reduce prices in an attempt to deter entry of new competitors. Using data for three broadly-defined network industries in 23 OECD countries and covering over 30 years, I show that such re-organization has sizable negative short-term effects on industry employment. The employment losses, which last at least 3 years, are larger when reforms are implemented during downturns and insignificant when they take place in upturns. These findings contrast with previous evidence that deregulation in retail distribution has no (or even positive) short-term employment effects. This discrepancy is likely driven by the much larger employment share of small incumbents, with no margins of efficiency improvement, in retail than in network industries (as well as many other industries). Evidence on the immediate effect of removing entry barriers on industry prices and productivity is consistent with the hypothesis that the initial contraction of industry employment is the result of incumbents re-organising and downsizing before the entry of new competitors.
Keywords: J23; L11; 330; barriers to entry; structural reforms; job destruction; short-term costs; optimal timing of reforms